1991
DOI: 10.1109/16.88525
|View full text |Cite
|
Sign up to set email alerts
|

Field-emitter arrays for vacuum microelectronics

Abstract: Public reporting burden for this colection of inlormation is estimated to average 1 hour po, response, mCuc~ng rrie tilie !0, fvicwnrg nslrucVOnS sea'dPNg existing data sources, gathering and maintaining the data needed, and compieting and reviewing the coiiecion o' niorratiorn Send oommne"•s rega',a"g this burden estimate or any other aspect of this collecton of information. inclumng suggestions for recucng in s burder, to Waslngton HeaO•uarte's Servtces, Directorate for Information Operations and Reports, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
145
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(147 citation statements)
references
References 25 publications
2
145
0
Order By: Relevance
“…Field emission cathodes are used as neutralizers for space propulsion devices and as electron sources for flat-panel displays, focused electron beams for electron microscopy, and neutralization for spacecraft mass spectrometry [6][7][8][9]. The motivation for the research reported here is the limited lifetime of many current microfabricated field emitters, with the exception of carbon nanotube cathodes, which have demonstrated impressive life tests [10].…”
mentioning
confidence: 99%
“…Field emission cathodes are used as neutralizers for space propulsion devices and as electron sources for flat-panel displays, focused electron beams for electron microscopy, and neutralization for spacecraft mass spectrometry [6][7][8][9]. The motivation for the research reported here is the limited lifetime of many current microfabricated field emitters, with the exception of carbon nanotube cathodes, which have demonstrated impressive life tests [10].…”
mentioning
confidence: 99%
“…An array of vertical field emitters forms a large-area flat electron source. 4,5 Unfortunately, the vertical structure may be undesirable for circuit implementation due to the difficulties in achieving geometrical dimensions such as gap spacing to be identical over all devices on the substrate. In contrast, the geometry of the planar structure ( Fig.…”
mentioning
confidence: 99%
“…6 This device will be designed to emit up to 1 A of electron current. Electron emission is achieved by applying a gate voltage of approximately 75-100 V between an array of millions of microscopic needle points and a gate electrode.…”
Section: Electron Emittermentioning
confidence: 99%